(untitled) (Research, Society and Development, 2019)
The objective of this article was to analyze the difficulties for implementation of eSocial in accounting organizations. The research method used was the quantitative, descriptive and survey. The study was carried out with a population of 913 accounting organizations from Greater Florianópolis/SC, resulting in a sample of 333 respondents, representing 36.47% of the population. The data collection instrument used was a questionnaire based on the surveys made available on the Google Forms® platform with 33 (thirty-three) closed questions, validated by three area teachers. The data collected were tabulated directly on the Google Forms® platform and the relative frequency distribution classified as descriptive statistics was used as the analysis technique for the results. As main results, it was observed that accounting professionals need more qualification, for the handling of eSocial. It should be noted that there is little understanding on the part of these about this new accessory obligation and even on the scope of this theme in the daily routine of the offices. It was concluded that the labor market needs professionals engaged and proactive, who seek continuous improvement, especially with regard to eSocial.